Avaliação na Escola Waldorf: análise das práticas e contribuições - Munhoz Junior, Irceu (2022)
The general goal of this research was to analyze the evaluation practices in Waldorf schools based on the research of authors, researchers, and theoreticians in the field of evaluation, in parallel with the consultation of subjects who were working in Waldorf Elementary School. What motivated us to carry out such studies was the lack of specific literature that could guide and, most importantly, mitigate debates around this especially important aspect of the teaching and learning process of Waldorf pedagogy. During this research, we related the concepts and theoretical approaches of specific lines of assessment to what is practiced in Waldorf schools, and we could see that Waldorf assessment practice includes some aspects and characteristics of formative assessment. However, the interviewed subjects were not aware of the theoretical foundations they were working with in their practice, that is, they did it very much through their pedagogical experience and subjectivity. The methodology was developed through reflective interviews that fostered comprehensive and spontaneous testimonies from the Waldorf teachers in question. Their contributions were in line with the hypotheses raised by this research and, together with the theoretical framework studied, gave us the conditions to build concrete notes and to reach final considerations that point to contributions of Waldorf evaluative practices to the theoretical foundations of formative assessment, that is, there are characteristics of formative assessment in the evaluative practices of Waldorf schools and many pedagogical elements and actions specific to this educational chain could enrich the theoretical foundations of formative assessment. Thus, this research produced scientific knowledge of great value for the awareness about the concepts involved in Waldorf evaluative practices, but also pointed out possible contributions of Waldorf pedagogy to the theoretical field of evaluation